2016
DOI: 10.1093/neuonc/now022
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress-inducing drugs sensitize glioma cells to temozolomide through downregulation of MGMT, MPG, and Rad51

Abstract: These findings provide a strong rationale for combining temozolomide with ER stress-inducing drugs as an alternative therapeutic strategy for glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…The current treatments applied to GBM induce ER proteostasis imbalance and thereby may ultimately contribute to the selection of an adapted cell population that is resistant to the initial treatment. Drugs inducing further ER stress (such as salinomycin) sensitize glioma cells to TMZ treatment through the down-regulation of MGMT, N-methylpurine DNA glycosylase (MPG), and RAD51, three gene products involved in DNA repair (217), indicating that TMZ-mediated toxicity through the DNA damage pathway may interfere with the ER stress response, although the precise underlying molecular mechanisms remain unclear. Another approach would be to classify cancer cells as showing a selective advantage on the basis of high basal ER stress signaling activity, as previously shown in the case of oncogene-induced cell transformation (218).…”
Section: Discussionmentioning
confidence: 99%
“…The current treatments applied to GBM induce ER proteostasis imbalance and thereby may ultimately contribute to the selection of an adapted cell population that is resistant to the initial treatment. Drugs inducing further ER stress (such as salinomycin) sensitize glioma cells to TMZ treatment through the down-regulation of MGMT, N-methylpurine DNA glycosylase (MPG), and RAD51, three gene products involved in DNA repair (217), indicating that TMZ-mediated toxicity through the DNA damage pathway may interfere with the ER stress response, although the precise underlying molecular mechanisms remain unclear. Another approach would be to classify cancer cells as showing a selective advantage on the basis of high basal ER stress signaling activity, as previously shown in the case of oncogene-induced cell transformation (218).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with 7p11.2, where both signals appear to be involved in EGFR regulation, the signals at 16p13.3 may have distinct molecular mechanisms. The non-GBM SNP rs3751667 is intronic within LMF1 , whereas the GBM SNP rs2562152 maps 3-kb telomeric to MPG that encodes a N-methylpurine DNA glycosylase whose expression is linked to temozolomide resistance in glioma (109). …”
Section: Chronological History Of Glioma Risk Loci Discoverymentioning
confidence: 99%
“…It has been shown to be down-regulated at the protein expression level when ER stress is induced via different means: tunicamycin (Yamamori et al, 2013), salinomycin (Xipell et al, 2016) or chronic hypoxia (Bindra et al, 2004;Cui et al, 2014). In Yamamori et al, a clear correlation was observed between the upregulation of phospho-eIF2α, indicating the level of ER stress, and the downregulation of Rad51 (Yamamori et al, 2013).…”
Section: Is There a "Biological" Effect?mentioning
confidence: 99%